IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DI SEKOLAH - Dewi Septiani Mandasari (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
This research was conducted at Karang Anyar 01 SDN Bangkalan. With the subject of the study were 34 fourth grade students. This study aims to determine the effect of contextual learning on the learning achievement of class IV students in civic education subjects at SDN Karang Anyar 01 Bangkalan. To find out the hypothesis proposed by the author is accepted and rejected. So the author uses data analysis with the t-test in the Paired Sample t-Test category, namely the t test used to determine whether or not there are differences in the mean between the two groups of pairs in pairs (related). The conclusion of the results of this study is "There is the effect of contextual learning on the learning achievement of class IV students in civic education subjects in SDN Karang Anyar 01 Bangkalan". Which shows t-count obtained at 9.0992. With a significant level of 5% it is worth 1,993. In other words, the price of t count is greater than t table  that is 9,0992 > 1,993 so automatically, the alternate hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.